Revisiting Hospitality: Opening doors beyond Derrida towards Nancy’s Inoperativity - Anastasia Tataryn (Law Text Culture, 2014)
This article explores the phenomenon of migrant labour2 through the lens of Jacques Derrida’s hospitality. Developing the concept of hospitality as an analytical and ethical question, this article suggests some limits of hospitality when applied to issues of migrant labour and offers an account of inoperative hospitality, which draws on Jean- Luc Nancy’s discussions of inoperative community. Hospitality, as discussed by Jacques Derrida in Of Hospitality (2000), challenges us to think of our relation to each other—to the stranger, the foreigner, even to the one without a name—in reference to a limit or a border. The concept of hospitality, or hospitality as ethics,3 has been explored as a theoretical notion to challenge existing hostile and restrictive immigration policies and practices. In 1996, in a speech on the sanspapiers movement in France, Derrida deplored the idea that there can be crimes of hospitality in ‘Derelictions of the Right to Justice’ (Derrida 2002a: 133). He urged, ‘we must [il faut] be able to rediscover a taste for living in a culture, a language, and a country in which hospitality is no longer a criminal offense’ (Derrida 2002a: 140). Seyla Benhabib and Bonnie Honig also have questioned hospitality for its potential to be mandated, or reflected, in migration, rights and citizenship policies.